Unpacking Attitudes on Immigrants and Refugees: A Focus on Household Composition and News Media Consumption - David De Coninck; Koen Matthijs; Marlies Debrael; Rozane De Cock; Leen d'Haenens (Media and Communication, 2019)
This study examines how household composition and news media consumption and trust are related to attitudes towards two minority groups—immigrants and refugees—in a representative sample of the adult population (n = 6000) in Belgium, Sweden, France, and the Netherlands. We find that Swedes hold the most positive attitudes towards both groups, while the French are found to be most negative. The Belgians and Dutch hold moderate attitudes. There is also evidence that attitudes on refugees are more negative than attitudes on immigrants in Sweden and France, but not in Belgium and the Netherlands. Using structural equation modeling, we find that household composition is not directly related to attitudes, but indirect effects through socio-economic status and media consumption indicate that singles hold more negative attitudes than couples. Public television consumption, popular online news consumption, and trust in media are positively related to attitudes, whereas commercial television consumption is negatively associated with them.